PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS STEM TERHADAP KEMAMPUAN LITERASI BIOLOGI SISWA KELAS X DI SMA NEGERI 1 SAMARINDA - Siti Nuraisyah; Sri Purwati (BIOLOVA, 2025)
This study was conducted to examine the effect of STEM-integrated Problem Based Learning learning model in improving the biological literacy skills of class X students of SMA Negeri 1 Samarinda. This study was designed to test the effect of independent variables (X) on the dependent variable (Y) with quantitative methods and quasi-experiment design with Pretest-Posttest Control Group. Group random sampling method to select class X-7 as the experimental group and class X-9 as the control group. Data were analyzed using the Independent Samples t test with a significance level of 5%. The application of PBL STEM brings better learning outcomes, as evidenced by data analysis significantly improves students' biological literacy skills. This is evidenced by the significance value of the t test which is smaller than 0.05, namely 0.036. Through the N Gain Test, it was revealed that the increase in learning outcomes was striking, reaching 0.74 and falling into the high category,which means that the STEM-based Problem Based Learning learning model was proven effective in improving the learning outcomes of class X students at SMA Negeri 1 Samarinda.